Pengaruh Metode Pembelajaran Outdoor Learning pada Materi Hidup Bersama Alam terhadap Kecerdasan Naturalistik Siswa Kelas III Sekolah Dasar: - - Ratih Prasetyaningrum; Wahyu Nugroho; Intan Susetyo Kusumo Wardhani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study was motivated by the suboptimal development of naturalistic intelligence among elementary school students, resulting from instruction that remains dominated by classroom-based activities and lacks direct interaction with the natural environment. The study aimed to determine the impact of the Outdoor Learning method—specifically focusing on the topic of "Living in Harmony with Nature"—on the naturalistic intelligence of third-grade elementary school students. A quantitative approach was employed using a quasi-experimental design, specifically a non-equivalent pretest-posttest control group design. The research sample consisted of 14 third-grade students from SDN 3 Wonoanti (experimental group) and 13 third-grade students from SDN 2 Sukorejo (control group). Data were collected using a naturalistic intelligence questionnaire that had passed validity and reliability testing. Data analysis included tests for normality, homogeneity, Independent Sample t-Tests, and N-Gain analysis. The results indicate a significant effect of the Outdoor Learning method on students' naturalistic intelligence (significance value of 0.000 < 0.05), leading to the rejection of H₀ and the acceptance of Hₐ. Effectiveness analysis showed an average N-Gain of 84.08 for the experimental group and 76.38 for the control group; while both fell into the "high" category, the experimental group achieved a greater improvement. Thus, the Outdoor Learning method—implemented through family medicinal plant cultivation activities—proved to be influential and more effective in enhancing the naturalistic intelligence of elementary school students.